Factors Affecting Calves Suckling Behavior - Radu Ionel Neamt (Scientific Papers Animal Science and Biotechnologies, 2015)
The aim of paper was to assess effects of environmental and physiological related factors on suckling behavior patterns. The study was carried out on 120 Romanian Spotted calves. Two behavioral traits were considered: total daily required interval and required interval for each meal. Traits were studied according to: calves viability, calving season, type of calving, calving ease and meal sequence. Significant differences were recorded for calves viability (viable vs morbid, p≤0.001), type of calving (single vs twinning, p≤0.001), and calving ease (eutocya vs dystocia, p≤0.001), being a proof of welfare, conferred by adaptability to new environment. No significant effect was recorded for season of calving (summer vs winter, p≥0.05). Significant differences concerning required suckling interval, were recorded between meals, both seasons. for viable (p≤0.001), morbid (p≤0.05), singles (p≤0.05) and calves born from eutocya births (p≤0.001). No significant differences (p≥0.05) recorded for twins and calves born from dystocia. Multifactorial regression model used, reveals that main effects on studied traits had viability (p≤0.001), type of calving (p≤0.01) and calving ease (p≤0.05). It is reasonable to assume that the knowledge of suckling behavior contributes to optimal management of calves. Knowledge of these factors helps to develop adequately systems to improve calves suckling response.